Design as Means of Countering Vandalism; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 19 : Lifelong Wellbeing in the World (WELLSO 2016) - Sokolov A.; Kukhta M. S. Maria Sergeevna; Kornienko M.; Kondratyeva Y.; Kukhta A. (2017, 2017)
Title screen